Agricultural transformations: early crop cultivation and farm animal domestication in South America, South Asia and India: EARLY CROP AND FARM ANIMAL DOMESTICATION (Indian Journal of Traditional Knowledge (IJTK), 2025)
The emergence of agriculture, around 10,000-14,000 years ago, is of great significance in human history, captivating archaeo-botanists and ethnologists. This significant transition originated with the global cultivation of plants and the domestication of animals. Regions such as South Asia and the Andean territories became pivotal hubs for the development and diversification of agricultural crops. Excavations in these regions yielded valuable insights from examining ethnobotanical and animal remains, revealing a diverse range of ancient cultivated plant materials. Vedic literature suggests that the Indian Subcontinent may have been the earliest hub for crop domestication and civilization. Interestingly, South America embraced agriculture almost simultaneously with the initial farmers in the Middle East. The presence of certain crops in the Americas and the Indian Subcontinent prior to European contact suggests shared exchanges or independent parallel domestication. These findings illuminate early stages of crop and animal domestication, offering insights into the agricultural practices and civilizations of South America, South Asia, and India.